Research | Open | Published:

# Coupled coincidence point theorems for generalized nonlinear contraction in partially ordered metric spaces

## Abstract

This paper is concerned with mixed g-monotone mappings in partially ordered metric spaces. We establish several coupled coincidence and coupled common fixed point theorems, which generalize and complement some known results. Especially, our main results complement some recent results due to Lakshmikantham and Ćirić. Two examples are given to illustrate the usability of our results.

Mathematics Subject Classification(2010): 47H10, 54H25.

## 1 Introduction

The existence of fixed points for monotone mappings in partially ordered metric spaces was initialed in [1], and such problems have been of great interest for many mathematicians (see, e.g, [26] and references therein).

The existence of coupled fixed points for mixed monotone mappings in partially ordered metric spaces was firstly studied by Bhaskar and Lakshmikantham [7], where some applications to periodic boundary value problems are studied. Since then, several authors have made contributions on such problems (see, e.g., [816]). Especially, Lakshmikantham and Ćirić [13] introduced a new concept of mixed g-monotone mapping:

Definition 1.1. Let (X, ≤) be a partially ordered set, F: X × XX and g: XX. We say F has the mixed g-monotone property if F is monotone g-non-decreasing in its first argument and is monotone g-non-increasing in its second argument, that is, for any x, y X,

$x 1 , x 2 ∈ X , g ( x 1 ) ≤ g ( x 2 ) implies F ( x 1 , y ) ≤ F ( x 2 , y ) ,$

and

$y 1 , y 2 ∈ X , g ( y 1 ) ≤ g ( y 2 ) implies F ( x , y 1 ) ≥ F ( x , y 2 ) .$

Moreover, Lakshmikantham and Ćirić [13] established several coupled coincidence and coupled fixed point theorems for mixed g-monotone mappings in a partially ordered metric space. In [13], one of the key assumption on the mixed g-monotone mapping F is:

$d ( F ( x , y ) , F ( u , v ) ) ≤ φ d ( g ( x ) , g ( u ) ) + d ( g ( y ) , g ( v ) ) 2$
(1.1)

for all x, y, u, v X with g(x) ≤ g(u) and g(y) ≥ g(v), where φ : [0, +∞) → [0, +∞) satisfies φ(t) < and $lim r → t + φ ( t ) for each t > 0.

The aim of this paper is to extend and complement the main results in [13] by replacing the contraction assumption (1.1) by a more general condition (see (A1) in Theorem 1). As one will see, our main results are generalizations and complements of some earlier results (see Examples and Remark 1). For some details see [17, 18].

## 2 Main results

Throughout the rest of this paper, we denote by the set of positive integers, and by (X, ≤, d) a complete partially ordered metric space, i.e., ≤ is a partial order on the set X, and d is a complete metric on X. Moreover, we endow the product space X × X with the following partial order: (u, v) ≤ (x, y) xu, yv.

Now, let us present one of our main results.

Theorem 2.1. Assume that g: XX is a continuous mapping, and F: X × XX is a continuous mapping with the mixed g-monotone property on X. Suppose that the following assumptions hold:

(A1) there exists a non-decreasing function ϕ : [0, +∞) → [0, +∞) such that$lim n → ∞ ϕ n ( t ) =0$for each t > 0, and d(F(x, y), F(u, v)) ≤ ϕ[M F,g (x, y, u, v)] for all x, y, u, v X with gxgu and gygv, where

(A2) there exist x0, y0 X such that gx0F (x0, y0) and F(y0, x0) ≤ gy0;

(A3) F(X ×X) g(X), and g and F are commuting, i.e., g(F(x, y)) = F(gx, gy) for all x, y X.

Then F and g have a coupled coincidence point, i.e., there exist x*, y* X such that F (x*, y*)= gx*and F(y*, x*) = gy*.

Proof. First, we claim that ϕ (t) < t for each t > 0. In fact, if ϕ (t0) ≥ t0 for some t0> 0, then, since ϕ is non-decreasing, ϕn(t0) ≥ t0 for all , which contradicts with $lim n → ∞ ϕ n ( t 0 ) =0$. In addition, it is easy to see that ϕ (0) = 0. Since F (X × X) g (X), one can construct two sequences {x n }, {y n } in X such that gx n = F (xn-1, yn-1), gy n = F (yn-1, xn-1), n . Observing that F has the mixed g-monotone property on X, by (A2), we get gx0gx1 ≤ ... ≤ gx n gxn+1≤ ... and ...≤ gyn+1gy n ≤ ... ≤ gy1gy0.

Now, by (A1), we have

$d ( g x n + 1 , g x n ) =d ( F ( x n , y n ) , F ( x n - 1 , y n - 1 ) ) ≤ϕ ( M F , g ( x n , y n , x n - 1 , y n - 1 ) ) ,$

and

$d ( g y n , g y n + 1 ) =d ( F ( y n - 1 , x n - 1 ) , F ( y n , x n ) ) ≤ϕ ( M F , g ( y n - 1 , x n - 1 , y n , x n ) ) ,$

where

Next, let us consider five cases.

Case I. M F,g (x n , y n , xn-1, yn-1) = max {d(gx n , gxn-1), d(gy n , gyn-1)}.

We have

$d ( g x n + 1 , g x n ) ≤ ϕ [ max { d ( g x n , g x n - 1 ) , d ( g y n , g y n - 1 ) } ] ,$
(2.1)

and

$d ( g y n , g y n + 1 ) ≤ ϕ [ max { d ( g x n , g x n - 1 ) , d ( g y n , g y n - 1 ) } ] .$
(2.2)

Case II. M F,g (x n , y n , xn-1, yn-1) = d(gx n , gxn+1).

We claim that M F,g (x n , y n , xn-1, yn-1) = d(gx n , gxn+1) = 0. In fact, if d(gx n , gxn+1) ≠ 0, then d(gxn+1, gx n ) ≤ ϕ [d(gxn+1, gx n )] < d(gxn+1, gx n ), which is contradiction. Since M F,g (x n , y n , xn-1, yn-1) = 0, we also have d (gy n , gyn+1) = 0. Then, it is obvious that (2.1) and (2.2) hold.

Case III. M F,g (x n , y n , xn-1, yn-1) = d (gy n , gyn+1).

Similar to the proof of Case II, one can also show that (2.1) and (2.2) hold.

Case IV. $M F , g ( x n , y n , x n - 1 , y n - 1 ) = d ( g x n - 1 , g x n + 1 ) 2$.

We also claim that d(gxn-1, gxn+1) = 0. In fact, if d(gxn-1, gxn+1) ≠ 0, then

$d ( g x n + 1 , g x n ) ≤ ϕ d ( g x n - 1 , g x n + 1 ) 2 < d ( g x n - 1 , g x n + 1 ) 2 ≤ d ( g x n - 1 , g x n ) 2 + d ( g x n , g x n + 1 ) 2 ,$

which gives that d (gxn+1, gx n ) < d (gxn-1, gx n ). Thus,

$M F ( x n , y n , x n - 1 , y n - 1 ) = d ( g x n - 1 , g x n + 1 ) 2

which contradicts with the definition of M F (x n , y n , xn-1, yn-1). So

$M F ( x n , y n , x n - 1 , y n - 1 ) = d ( g x n - 1 , g x n + 1 ) 2 = 0 .$

Thus, d (gx n , gxn+1) = d (gy n , gyn+1) = 0, which means that (2.1) and (2.2) hold.

Case V. $M F , g ( x n , y n , x n - 1 , y n - 1 ) = d ( g y n - 1 , g y n + 1 ) 2$.

By using a similar argument to Case IV, one can also show that (2.1) and (2.2) hold. Now, by (2.1) and (2.2), we have for all n ,

$max { d ( g x n + 1 , g x n ) , d ( g y n , g y n + 1 ) } ≤ ϕ [ max { d ( g x n , g x n - 1 ) , d ( g y n , g y n - 1 ) ) } ] ≤ ϕ n [ max { d ( g x 1 , g x 0 ) , d ( g y 1 , g y 0 ) ) } ] .$
(2.3)

Let ε > 0 be fixed. Without loss of generality, one can assume that

$max { d ( g x 1 , g x 0 ) , d ( g y 1 , g y 0 ) ) }≠0.$

In fact, if this is not true, then

$g x 0 = g x 1 = F ( x 0 , y 0 ) , g y 0 = g y 1 = F ( y 0 , x 0 ) ,$

i.e., x0, y0 is a coupled coincidence point of F and g. Since lim n→∞ ϕn(t) = 0 for each t > 0, by using (2.3), there exists N such that for all n > N,

$max { d ( g x n + 1 , g x n ) , d ( g y n , g y n + 1 ) } < ε - ϕ ( ε ) .$
(2.4)

Next, let us prove that for all n > N,

$max { d ( g x n + p , g x n ) , d ( g y n , g y n + p ) } ≤ ε , ∀ p ∈ ℕ ,$
(2.5)

and

$max { d ( g x n + p - 1 , g x n + 1 ) , d ( g y n + 1 , g y n + p - 1 ) } ≤ ϕ ( ε ) , ∀ p ≥ 3 .$
(2.6)

For p = 1, it follows directly from (2.4) that (2.5) holds. For p = 2, (2.5) follows from

$max { d ( g x n + 2 , g x n ) , d ( g y n + 2 , g y n ) } ≤ max { d ( g x n + 2 , g x n + 1 ) , d ( g y n + 2 , g y n + 1 ) } + max { d ( g x n + 1 , g x n ) , d ( g y n + 1 , g y n ) } ≤ ϕ [ max { d ( g x n + 1 , g x n ) , d ( g y n + 1 , g y n ) } ] + ε - ϕ ( ε ) ≤ ϕ ( ε ) + ε - ϕ ( ε ) = ε ,$

where (2.3) and (2.4) are used. Let us show that (2.5) and (2.6) hold for p = 3. Firstly, by (2.3) and (2.4), we have

$max { d ( g x n + 2 , g x n + 1 ) , d ( g y n + 2 , g y n + 1 ) } ≤ ϕ [ max { d ( g x n + 1 , g x n ) , d ( g y n + 1 , g y n ) } ] ≤ ϕ ( ε ) ,$

which means that (2.6) holds for p = 3. Secondly, by (A1), we have

$max { d ( g x n + 3 , g x n + 1 ) , d ( g y n + 1 , g y n + 3 ) } ≤ ϕ [ z n ] ,$
(2.7)

where

We claim that z n ≤ ε. In fact, if z n = max {d(gxn+2, gx n ), d(gy n , gyn+2)}, then by (2.5) (p = 2), z n ε; if z n = max {d(gxn+2, gxn+3), d(gyn+2, gyn+3)}, then by (2.3) and (2.4), z n ϕ2 (ε) ≤ ε; if z n = max {d(gx n , gxn+1), d(gy n , gyn+1)}, then (2.4) gives that z n ε; if $z n = d ( g x n + 2 , g x n + 1 ) + d ( g x n , g y n + 3 ) 2$, then by (2.7), there holds $d ( g x n + 3 , g x n + 1 ) ≤ d ( g x n + 2 , g x n + 1 ) + d ( g x n , g y n + 3 ) 2 ≤ ϕ ( ε ) + d ( g x n , g y n + 3 ) 2$, which yields that

$d ( g x n , g x n + 3 ) ≤ d ( g x n + 3 , g x n + 1 ) + d ( g x n + 1 , g x n ) ≤ ϕ ( ε ) + d ( g x n , g x n + 3 ) 2 + ε - ϕ ( ε ) = ε - ϕ ( ε ) 2 + d ( g x n , g x n + 3 ) 2 ,$

and thus, $z n = d ( g x n + 2 , g x n + 1 ) + d ( g x n , g x n + 3 ) 2 ≤ ϕ ( ε ) 2 + d ( g x n , g x n + 3 ) 2 ≤ε$; if $z n = d ( g y n + 2 , g y n + 1 ) + d ( g y n , g y n + 3 ) 2$, one can similarly show that z n ε. Hence, in all cases, z n ε. Then, by (2.4) and (2.7), we get

$max { d ( g x n + 3 , g x n ) , d ( g y n , g y n + 3 ) } ≤ max { d ( g x n + 3 , g x n + 1 ) , d ( g y n + 1 , g y n + 3 ) } + max { d ( g x n + 1 , g x n ) , d ( g y n , g y n + 1 ) } ≤ ϕ ( ε ) + ε - ϕ ( ε ) = ε ,$

i.e., (2.5) holds for p = 3.

Now, suppose that (2.5) and (2.6) hold for all pk - 1. Let us prove that (2.5) and (2.6) hold for p = k. By (A1), (2.3), (2.4), (2.5) for p = k - 2, k - 1 and for p = k - 1 we conclude

i.e., (2.6) holds for p = k. In addition, since max {d(gx n+k , gxn+1), d(gyn+1, gy n+k )} ≤ ϕ[w n ], where w n = max {d(gxn+k-1, gx n ), d(gy n , gyn+k-1), d(gxn+k-1, gx n+k ), d(gyn+k-1, gy n+k ), d(gx n , gxn+1),

by similar proof to that of z n (see (2.7)), one can show that w n ε. Thus,

$max { d ( g x n + k , g x n ) , d ( g y n , g y n + k ) } ≤ max { d ( g x n + k , g x n + 1 ) , d ( g y n + 1 , g y n + k ) } + max { d ( g x n + 1 , g x n ) , d ( g y n , g y n + 1 ) } ≤ ϕ ( ε ) + ε - ϕ ( ε ) = ε ,$

i.e., (2.6) holds for p = k.

Now, we have proved that (2.5) holds for all p , which means that {gx n } and {gy n } are Cauchy sequences in X. Then, by the completeness of X, there exist x*, y* X such that limn→∞gx n = x*, limn→∞gy n = y*. By (A3), g commutes with F. So g (gxn+1) = g (F (x n , y n )) = F (gx n , gy n ) and g (gyn+1) = g (F (y n , x n )) = F (gy n , gx n ). Letting n → ∞ and noticing that F and g are continuous, we get g (x*) = F (x*, y*), g (y*) = F (y*, x*).    □

We demonstrate the use of Theorems 2.1 with the help of the following examples. It will show also that our theorem is more general than some other known coupled fixed point results ([7, 13]).

Examples: (1) Let X = be endowed with usual order, d (x, y) = |x - y|, $F ( x , y ) = 1 4 x- 1 5 y,gx= 1 2 x,ϕ ( t ) = 9 10 t$. We have that mappings F, g and ϕ satisfy all conditions of the Theorem 2.1, but they do not satisfy (1.1). Therefore F and g have a coupled coincidence point. Here (0, 0) is the coupled coincidence point of F and g. Indeed, for xu, yv we have

$d ( F ( x , y ) , F ( u , v ) ) = 1 4 ( x - u ) + 1 5 ( v - y ) ≤ 9 20 max { | x - u | , | y - v | } = 9 10 max x 2 - u 2 , y 2 - v 2 = 9 10 max { d ( g x , g u ) , d ( g y , g v ) } .$

However, if (1.1) is true, then we have

$1 4 = d ( 0 , 1 4 ) = d ( F ( 0 , 0 ) , F ( 1 , 0 ) ) ≤ φ d ( g 0 , g 1 ) + d ( g 0 , g 0 ) 2 = φ ( 1 4 ) < 1 4 ,$

which is a contradiction. Hence, the existence of a coupled coincidence point of F and g cannot be obtained by the result from [13].

(2) If in the previous example we take $F ( x , y ) = 1 2 x- 1 3 y$, gx = x, $ϕ ( t ) = 5 6 t$, then we obtain that mappings F, g and ϕ satisfy all conditions of the Theorem 2.1, but they do not satisfy the conditions of corresponding Theorem from [7]. Indeed, in this case we have

$d ( F ( x , y ) , F ( u , v ) ) = 1 2 ( x - u ) + 1 3 ( v - y ) ≤ 5 6 max { | x - u | , | y - v | } .$

On the other hand, for x = 1, y = u = v = 0, we obtain

$d ( F ( 1 , 0 ) , F ( 0 , 0 ) ) = 1 2 > k 2 = k 2 ( d ( 1 , 0 ) + d ( 0 , 0 ) ) ,$

for all k [0, 1). Also, this example shows that the existence of a coupled coincidence point of F and g cannot be obtained by the result from [7].

In the case that F is not continuous, one can use the following theorem:

Theorem 2.2. Suppose all the assumptions of Theorem 2.1. except for the continuity of F are satisfied. Moreover, assume that g is monotone under the partial order, and X has the following properties:

( a ) if an non-decreasing sequence {x n } converges to X in X, then x n x for all n ;

( b ) if an non-increasing sequence {y n } converges to y in X, then yy n for all n .

Then the conclusions of Theorem 2.1 also hold.

Proof. Let {x n }, {y n }, x*, y* be as in Theorem 1. Then limn→∞gx n = x* and limn→∞gy n = y*.

It remains to prove that g (x*) = F (x*, y*) , g (y*) = F (y*, x*) .

By the proof of Theorem 1, we have gx0gx1 ≤ ... ≤ gx n gxn+1≤ ... and ... ≤ gyn+1gy n ...gy1gy0. It follows from the assumptions (a) and (b) that gx n x* and y*gy n for all n . In addition, without loss of generality, one can assume that g is non-decreasing about the partial order ≤ . Then g2x n gx* and gy*g2y n for all n , where g2z := g (gz) for all z X.

Next, using (A1), we obtain

$d ( F ( x * , y * ) , g 2 x n + 1 ) = d ( F ( x * , y * ) , F ( g x n , g y n ) ) ≤ ϕ [ a n ] ,$
(2.8)
(2.9)

where

Now, we claim that

$max { d ( g x * , F ( x * , y * ) ) , d ( g y * , F ( y * , x * ) ) } = 0 .$
(2.10)

If this not true, then max {d (gx*, F (x*, y*)) , d (gy*, F (y*, x*))} > 0. Since limn→∞gx n = x*, limn→∞gy n = y*, there exists N such that for all n > N,

$a n = b n = max { d ( g x * , F ( x * , y * ) ) , d ( g y * , F ( y * , x * ) ) } .$

Combining this with (2.8) and (2.9), we get for all n > N,

$max { d ( F ( x * , y * ) g 2 x n + 1 ) , d ( g 2 y n + 1 , F ( y * , x * ) ) } ≤ ϕ [ max { d ( g x * , F ( x * , y * ) ) , d ( g y * , F ( y * , x * ) ) } ] .$

Letting n → ∞ it follows that

$max { d ( g x * , F ( x * , y * ) ) , d ( g y * , F ( y * , x * ) ) } ≤ ϕ [ max { d ( g x * , F ( x * , y * ) ) , d ( g y * , F ( y * , x * ) ) } ] .$

This is a contradiction. So (2.10) holds. Then, it follows that gx* = F (x*, y*) and gy* = F (y*, x*) .

Remark 1. It is easy to see that Theorems 2.1. and 2.2. are generalizations of corresponding results in [7]. In addition, Theorems 2.1. and 2.2. extends some earlier results for non-decreasing mappings in partially ordered metric spaces. For example, let g = I (the identity map), F be non-decreasing under the first argument and be independent of the second argument, one can deduce [2, Theorem 2.2].

In some cases, one can show that the coupled coincidence point is a coupled common fixed point. For example, we have the following result:

Theorem 2.3. Suppose all the assumptions of Theorem 2.1. (or Theorem 2.2.) are satisfied. Moreover, assume that

(A4) the M F,g (x, y, u, v) in (A1) equals to

$max d ( g x , g u ) , d ( g y , g v ) , d ( g x , F ( u , v ) ) + d ( g u , F ( x , y ) ) 2 , d ( g y , F ( v , u ) ) + d ( g v , F ( y , x ) ) 2 ;$

(A5) for every (x1, x2), (y1, y2) X × X, there exists (z1, z2) X × X such that (gz1, gz2) is comparable to (gx1, gx2) and (gy1, gy2).

Then F and g have a unique coupled common fixed point, i.e., there exists a unique (a, b) X × X such that F (a, b) = ga = a and F (b, a) = gb = b.

Proof. By Theorem 2.1. (or Theorem 2.2.), we know that F and g have a coupled coincidence point, i.e., there exist x*, y* X such that F (x*, y*) = gx* and F (y*, x*) = gy*. Let (x*, y*) X × X be also a coupled coincidence point of F and g. First, let us prove that

$g x * = g x * , g y * = g y * .$
(2.11)

By (A5), there exists (u0, v0) X × X such that (gu0, gv0) is comparable to (gx*, gy*) and (gx*, gy*) . Let

$g u n = F ( u n - 1 , v n - 1 ) , g v n = F ( v n - 1 , u n - 1 ) , n = 1 , 2 , …$

Since F is mixed g-monotone and (gu0, gv0) is comparable to (gx*, gy*), we claim that (F (u0, v0) , F (v0, u0)) is comparable to (F (x*, y*) , F (y*, x*)) , i.e., (gu1, gv1) is comparable to (gx*, gy*) . In fact, if

$( g u 0 , g v 0 ) ≤ ( g x * , g y * ) ,$

i.e.,

and thus

which means that

$( g u 1 , g v 1 ) ≤ ( g x * , g y * ) ;$

if (gu0, gv0) = (gx*, gy*), by a similar proof, we can get (gu1, gv1) ≥ (gx*, gy*). In addition, analogously to the above proof, one can also show that (gu1, gv1) is comparable to (gx*, gy*) . Hence, by induction, one can prove that for each n , (gu n , gv n ) is comparable to (gx*, gy*) and (gx*, gy*) .

Now, by (A4), we have

$max { d ( g x * , g u n + 1 ) , d ( g y * , g v n + 1 ) } = max { d ( F ( x * , y * ) , F ( u n , v n ) ) , d ( F ( y * , x * ) , F ( v n , u n ) ) } ≤ ϕ [ c n ] ,$

where

$c n = max d ( g x * , g u n ) , d ( g y * , g v n ) , d ( g x * , g u n + 1 ) + d ( g x * , g u n ) 2 , d ( g y * , g v n + 1 ) + d ( g y * , g v n ) 2 .$

We claim that c n = max {d (gx*, gu n ), d (gy*, gv n )}. In fact, if $c n = d ( g x * , g u n + 1 ) + d ( g x * , g u n ) 2 >0$, then $d ( g x * , g u n + 1 ) ≤ϕ [ c n ] < d ( g x * , g u n + 1 ) + d ( g x * , g u n ) 2$, which means that d (gx*, gun+1) < d (gx*, gu n ), and thus $c n = d ( g x * , g u n + 1 ) + d ( g x * , g u n ) 2 . This is a contradiction. In addition, if $c n = d ( g y * , g v n + 1 ) + d ( g y * , g v n ) 2 >0$, one can also show that there is a contradiction. Thus we have

$max { d ( g x * , g u n + 1 ) , d ( g y * , g v n + 1 ) } ≤ϕ [ max { d ( g x * , g u n ) , d ( g y * , g v n ) } ] .$

Then, it follows that

$max { d ( g x * , g u n + 1 ) , d ( g y * , g v n + 1 ) } ≤ ϕ n + 1 [ max { d ( g x * , g u 0 ) , d ( g y * , g v 0 ) } ] .$

Analogously to the above proof, one can also show that

$max { d ( g x * , g u n + 1 ) , d ( g y * , g v n + 1 ) } ≤ ϕ n + 1 [ max { d ( g x * , g u 0 ) , d ( g y * , g v 0 ) } ] .$

Letting n → ∞, we get gx* = limn→∞gu n+1 = gx*, gy* = limn→∞gv n+1 = gy*.

Since F (gx*, gy*) = g (gx*) and F (gy*, gx*) = g (gy*), (gx*, gy*) is a coupled coincidence point of F and g, thus, by (2.11), we have g (gx*) = gx*, g (gy*) = gy*. Let a = gx* and b = gy*. Then F (a, b) = F (gx*, gy*) = g (gx*) = ga = a and F (b, a) = F (gy*, gx*) = g (gy*) = gb = b. It remains to show the uniqueness. Let (c, d) X × X such that F (c, d) = gc = c and F (d, c) = gd = d. Since (a, b) and (c, d) are both coupled coincidence points of F and g, by (2.11), we get ga = gc, gb = gd, and thus a = c, b = d. This completes the proof.

## References

1. 1.

Ran ACM, Reurings MCB: A fixed point theorem in partially ordered sets and some application to matrix equations. Proc Am Math Soc 2004, 132: 1435–1443. 10.1090/S0002-9939-03-07220-4

2. 2.

Agarwal RP, El-Gebeily MA, O'Regan D: Generalized contractions in partially ordered metric spaces. Appl Anal 2008, 87: 109–116. 10.1080/00036810701556151

3. 3.

Kadelburg Z, Pavlović M, Radenović S: Common fixed point theorems for ordered contractions and quasicontractions in ordered cone metric spaces. Comput Math Appl 2010, 59: 3148–3159. 10.1016/j.camwa.2010.02.039

4. 4.

Long W, Rhoades BE, Rajović M: Coupled coincidence points for two mappings in metric spaces and cone metric spaces. Fixed Point Theory Appl 2012, 2012: 66. 10.1186/1687-1812-2012-66

5. 5.

Nieto JJ, Lopez RR: Contractive mapping theorems in partially ordered sets and applications to ordinary differential equations. Order 22: 223–239.

6. 6.

O'Regan D, Petrusel A: Fixed point theorems for generalized contractions in ordered metric spaces. J Math Anal Appl 2008, 341: 1241–1252. 10.1016/j.jmaa.2007.11.026

7. 7.

Gnana Bhaskar T, Lakshmikantham V: Fixed point theorems in partially ordered metric spaces and applications. Nonlinear Anal 2006, 65: 1379–1393. 10.1016/j.na.2005.10.017

8. 8.

Abbas M, Ali Khan M, Radenović S: Common coupled fixed point theorems in cone metric spaces for w-compatible mappings. Appl Math Comput 2010, 217: 195–202. 10.1016/j.amc.2010.05.042

9. 9.

Abbas M, Nazir T, Radenović S: Common fixed points of four maps in partially ordered metric spaces. Appl Math Lett 2011, 24: 1520–1526. 10.1016/j.aml.2011.03.038

10. 10.

Aydi H, Postolache M, Shatanawi W: Coupled fixed point results for ( ψ , ϕ )-weakly contractive mappings in ordered G-metric spaces. Comput Math Appl 2012, 63: 298–309. 10.1016/j.camwa.2011.11.022

11. 11.

Aydi H, Karapinar E, Shatanawi W: Coupled fixed point results for ( ψ , ϕ )-weakly contractive condition in ordered partial metric spaces. Comput Math Appl 2011, 62: 4449–4460. 10.1016/j.camwa.2011.10.021

12. 12.

Cho YJ, Rhoades BE, Saadati R, Samet B, Shatanawi W: Nonlinear coupled fixed point theorems in ordered generalized metric spaces with integral type. Fixed Point Theory Appl 2012, 2012: 8. doi:10.1186/1687–1812–2012–8.

13. 13.

Lakshmikantham V, Cirić L: Coupled fixed point theorems for nonlinear contractions in partially ordered metric spaces. Nonlinear Anal 2009, 70: 4341–4349. 10.1016/j.na.2008.09.020

14. 14.

Nashine HK, Shatanawi W: Coupled common fixed point theorems for a pair of commuting mappings in partially ordered complete metric spaces. Comput Math Appl 2011, 62: 1984–1993. 10.1016/j.camwa.2011.06.042

15. 15.

Shatanawi W: Fixed point theorems for nonlinear weakly C-contractive mappings in metric spaces. Math Comput Model 2011, 54: 2816–2826. doi:10.1016/j.mcm.2011.06.069 10.1016/j.mcm.2011.06.069

16. 16.

Shatanawi W, Samet B, Abbas M: Coupled fixed point theorems for mixed monotone mappings in ordered partial metric spaces. Math Comput Model 2012, 55: 680–687. 10.1016/j.mcm.2011.08.042

17. 17.

Choudhury BS, Kundu A: A coupled coincidence point result in partially ordered metric spaces for compatible mappings. Nonlinear Anal 2010, 73: 2524–2531. 10.1016/j.na.2010.06.025

18. 18.

Samet B: Coupled fixed point theorems for a generalized Meir-Keeler contraction in partially ordered metric spaces. Nonlinear Anal 2010, 72: 4508–4517. 10.1016/j.na.2010.02.026

## Acknowledgements

The authors thank the referees for their valuable comments that helped to improve the text. Hui-Sheng Ding acknowledges support from the NSF of China (11101192), the Key Project of Chinese Ministry of Education (211090), the NSF of Jiangxi Province (20114BAB211002), the Jiangxi Provincial Education Department (GJJ12173), and the Program for Cultivating Youths of Outstanding Ability in Jiangxi Normal University. Third author is thankful to the Ministry of Science and Technology Development of Serbia.

## Author information

Correspondence to Hui-Sheng Ding.

### Competing interests

The authors declare that they have no competing interests.

### Authors' contributions

All authors contributed equally and significantly in writing this paper. All authors read and approved the final manuscript.

## Rights and permissions

Reprints and Permissions